The BIM implementation journey in Nuevo Leon, Mexico - DAVIS CAMPOY, MIGUEL RODOLFO; Lara-Prieto, Vianney; Yeomans Galli, Laura María; García Rodríguez, Salvador (LACCEI, 2024)
Digitalization in the construction industry in Mexico is limited. Despite significant advancements in technological development, computing power, and network connectivity, productivity in the construction sector appears not to change, while the manufacturing industry, for example, has embraced digital transformation. While there are notable differences between both, there certainly are efficiencies that should be harnessed. In Mexico, there is still no law that obligates State governments to work on public construction projects using BIM methodologies. Therefore, to bring about a change, government initiative is required to form a working group where public, private, and academic institutions collaborate to implement BIM in public and private construction projects. In this regard, the government of the state of Nuevo Leon took the initiative to form a working group involving both public and private institutions, playing a crucial role in implementing the BIM Methodology in both public and private construction. The goal is to develop high-quality projects in less time and at lower costs, leveraging the technological resources and human capital from the public and private sectors through the implementation of the BIM Methodology in the state of Nuevo Leon. This work presents a methodology, including the preliminary results of the pilot project, describing the roadmap to implement BIM and highlighting its benefits.Keywords—BIM, Higher Education, Educational Innovation, Digitalization, Public Construction Projects, Construction Management